Local Economic Resistance and the Struggle Against Global Capitalism: Evidence from the Rammang-Rammang Tourism Area - Hana Tuo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Contemporary economic systems increasingly prioritize accumulation and growth, reshaping social and cultural sectors, including tourism. While tourism is often promoted as a development strategy capable of generating prosperity, its market-oriented orientation frequently reproduces social inequalities and uneven economic benefits at the local level. This article examines the transformation of the local economy in the Rammang-Rammang tourism area, South Sulawesi, following community resistance against karst mining in 2007. Drawing on a critical qualitative approach, the study employs Critical Discourse Analysis (CDA) following Norman Fairclough’s framework to analyze how narratives of community-based tourism, empowerment, and local economy are produced, negotiated, and contested. Data were collected through in-depth interviews, participant observation, and documentation of policy texts, media narratives, and discursive artefacts related to tourism development. The findings indicate that post-resistance economic transformation in Rammang-Rammang does not evolve linearly toward an egalitarian community economy. Instead, tourism development becomes a contested arena in which collective practices and everyday forms of resistance coexist with emerging inequalities, concentration of economic access, and tendencies toward local capitalism. Although community-based economic practices and subsistence activities continue to function as mechanisms of autonomy and resistance, they remain fragmented and vulnerable to discursive and structural co-optation. This study argues that community-based tourism should be understood not as a purely alternative economic model, but as a dynamic space of negotiation between resistance, adaptation, and capitalist domination. The article contributes to critical debates on counter-economy, power relations, and equitable development in tourism-based communities in the Global South.